URBAN ART SCENE IN MADRID: HOW CAN CONTEMPORARY ART BE USED FOR TOURISM? - Perera, Punartha Jeevana (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
Urban art (UA) is a contemporary art form which was developed in cities. While UA growth in certain cities has been faster, the progression of UA in most cities has faced opposition. The described project explores the current context of the progression of UA in Madrid. Furthermore, the research gives reason to UA’s capability as a tourism tool in Madrid, and identifies the stakeholders related to UA who should benefit. Project is carried out using qualitative methodology through an exploratory approach and is completed with the use of more primary source data. Observations, short questionnaires and interviews are the main instruments used in gathering the primary source data, while document analysis is used to process additional secondary source data. The results show that Madrid is full of different types of UA, and UA can be further developed as a tourism tool in the city. The urban artists are creating their own UA pieces both legally and illegally while facing obstacles, even though impediments have reduced. However, the Investigation concludes that Madrid’s UA can be further developed through strong support from local policy makers by giving the direct benefits of this development to local UA stakeholders.